2005
DOI: 10.1124/jpet.104.082792
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibitor SC-236 [4-[5-(4-Chlorophenyl)-3-(trifluoromethyl)-1-pyrazol-1-l] Benzenesulfonamide] Suppresses Nuclear Factor-κB Activation and Phosphorylation of p38 Mitogen-Activated Protein Kinase, Extracellular Signal-Regulated Kinase, and c-Jun N-Terminal Kinase in Human Mast Cell Line Cells

Abstract: SC-236 [4-[5-(4-chlorophenyl)-3-(trifluoromethyl)-1-pyrazol-1-l]benzenesulfonamide; C 16 H 11 ClF 3 N 3 O 2 S] is a highly selective cyclooxygenase (COX)-2 inhibitor. However, the exact mechanism that accounts for the anti-inflammatory effect of SC-236 is not completely understood. The aim of the present study was to elucidate whether and how SC-236 modulates the inflammatory reaction in a stimulated human mast cell (HMC) line, HMC-1. SC-236 inhibited the expression of tumor necrosis factor-␣, interleukin (IL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In the study by Dogan et al (20), such a blockade occurred only when the dose of SC-236 was substantially higher (40 mg/kg) than the doses (1-15 mg/kg) known to selectively block COX-2 in vivo (31,53). At such a high dose, SC-236 might have inhibited COX-1, or it might have exerted COX-unrelated effects (39). Although the study by Zhang et al (90) employed a lower dose of SC-236 (5 mg/kg), it was limited by marked stress hyperthermia following intraperitoneal drug administration, which overlapped substantially with the early hypothermic response to LPS, thus making the results difficult to interpret.…”
Section: Effects Of Cox-1 and Cox-2 Inhibitors On Lps-induced Responsesmentioning
confidence: 99%
“…In the study by Dogan et al (20), such a blockade occurred only when the dose of SC-236 was substantially higher (40 mg/kg) than the doses (1-15 mg/kg) known to selectively block COX-2 in vivo (31,53). At such a high dose, SC-236 might have inhibited COX-1, or it might have exerted COX-unrelated effects (39). Although the study by Zhang et al (90) employed a lower dose of SC-236 (5 mg/kg), it was limited by marked stress hyperthermia following intraperitoneal drug administration, which overlapped substantially with the early hypothermic response to LPS, thus making the results difficult to interpret.…”
Section: Effects Of Cox-1 and Cox-2 Inhibitors On Lps-induced Responsesmentioning
confidence: 99%
“…69 -71 These intracellular pathways have also been shown to play a significant role in smooth muscle cells, mast cells, and endothelial cells. [72][73][74] Hence, the expression of PGE 2 -synthesizing enzymes is most likely regulated by a complex network of cytokines and signal transduction pathways, as well as by cross-talk interactions among cells.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Several studies suggested that suppression of MC NF-kB is responsible for reducing inflammatory mediators released during inflammation. [29][30][31] Thus we asked whether iTreg cells can modulate NF-kB signaling in MCs. To this end, BMMCs were cocultured with iTreg cells (2:1 ratio) for 24 hours, followed by stimulation with PMACI for another 6 hours.…”
Section: Itreg Cells Inhibit Proinflammatory Cytokine Release In Mcs mentioning
confidence: 99%